2016
DOI: 10.1007/s11554-016-0569-z
|View full text |Cite
|
Sign up to set email alerts
|

Real-time raindrop detection based on cellular neural networks for ADAS

Abstract: A core aspect of advanced driver assistance systems (ADAS) is to support the driver with information about the current environmental situation of the vehicle. Bad weather conditions such as rain might occlude regions of the windshield or a camera lens and therefore affect the visual perception. Hence, the automated detection of raindrops has a significant importance for video-based ADAS. The detection of raindrops is highly time critical since video pre-processing stages are required to improve the image quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Therefore, the history of inputs might affect the outputs. Thus, the used model should have a memory that considers the history of its inputs; this is considered by our CNN model; ( b ) because of the high parallelism of the CNN processor, this makes our CNN model a real-time model than can be implemented on embedded platforms easily [ 54 ]; and ( c ) using the paradigm of CNN for classification purposes showed promising results in the state-of-the-art [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the history of inputs might affect the outputs. Thus, the used model should have a memory that considers the history of its inputs; this is considered by our CNN model; ( b ) because of the high parallelism of the CNN processor, this makes our CNN model a real-time model than can be implemented on embedded platforms easily [ 54 ]; and ( c ) using the paradigm of CNN for classification purposes showed promising results in the state-of-the-art [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also shown that combining those traditional methods with dynamical neural networks like cellular neural networks can result in a significant performance improvement. For example, Al Machot et al [ 11 ] showed that combining SVM with cellular neural networks considerably improves the SVM performance; this new resulting hybrid model can thus be used as a very fast and robust detector/classifier instead of using the sole SVM model.…”
Section: Introductionmentioning
confidence: 99%
“…CNN is chosen for the method of detection in medical image processing due to its efficiency in pattern recognition and image processing [16]- [20]. CNN algorithm is also applied in memristor [21]- [23], srobotics [24], ditributed network [25] and raindrop detection [26]. Hence, in this study, a new detection method by using CNN algorithm will be used to detect the cancerous cervical cells in a shorter time.…”
Section: Introductionmentioning
confidence: 99%